Achieving HIV epidemic control through accelerating efforts to expand access to pre-exposure prophylaxis for people who inject drugs - Nishimoto, Lirica; Olisa, Adaobi Lisa; Imohi, Philip; Chang, Judy; Obermeyer, Chris; Kabwali, Dama; Akolo, Christopher (Frontiers in Reproductive Health, 2024)
The world is not on track to reach the majority of the UNAIDS 2025 targets, and people who inject drugs (PWID) continue to be left behind, hindered by counterproductive law enforcement practices, punitive laws, economic distress, and social stigma and discrimination. Poor access to HIV pre-exposure prophylaxis (PrEP) among PWID is nested within the limited access to broader harm reduction services, including needle and syringe programs, opioid overdose management, opioid agonist therapy (also known as medication-assisted treatment), and condoms. Among PWID, women who inject drugs are disproportionately affected and face additional gender-based barriers. Intersections between PWID and other key and priority population groups also exist. Although the prioritization of PWID for new PrEP products like the dapivirine vaginal ring and injectable cabotegravir has lagged in research, studies have shown that PWID find injectable and long-acting options acceptable and preferrable, including among women who inject drugs. While new PrEP products introduce new opportunities, equity in access must be assured for optimized impact toward achieving epidemic control. Programming for services must engage and empower PWID community leadership to address the structural barriers to services, implement community-led, differentiated, and integrated service modalities, and offer the choice of all harm reduction options to close the equity gaps in health outcomes. While waiting for necessary evidence and approvals, programs should work together with the PWID community to prioritize, expand, and facilitate efforts and investments toward increased access to and integration of PrEP and all recommended harm reduction services for PWID.